PERSONALITY TEST APPLICATION USING MICROSOFT VISUAL BASIC 6.0 - F.X Daryadi; Don Elsyafitra, Skom. (Jurnal Sistem Informasi, 2005)
Progress in the field of computers in today's rapidly computerized community. These benefits not only enjoyed by large companies but also by small companies and even individuals. One progress computer is a computer application view. In this scientific writing writer tries to make the application simple personality test to help give the image extent to which an individual's personality development. Works about - about the quiz on this test was made by computerized, and test results are also programmed in such a way that can be seen immediately after the test do so more quickly, practical and efficient than manual work.